2018
DOI: 10.15171/ehem.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical degradation of azithromycin in aqueous solution

Abstract: Background: The presence of pharmaceutical substances and their residual in water resources is an important environmental concern. Azithromycin, an antibiotic that is used for the treatment of infectious diseases, is a pollutant agent in the wastewater. The aim of this study was to investigate azithromycin degradation in aqueous solution through ultrasonic process in the presence of zinc oxide nanoparticles as catalysts. Methods: Sonocatalytic experiments were performed at variable conditions including pH (3-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“… Yazdani and Sayadi (2018) , in studies using sonochemistry in AZI degradation, have shown that the pH has a significant effect on the AZI degradation, while temperature and contact time have a less significant effect. The experimental conditions in which 90.59% AZI degradation was achieved were temperature = 40 ⁰C, initial concentration of AZI = 20 mg L −1 , pH = 3, after 15 min and using low-frequency ultrasound (35 kHz), as shown in Fig.…”
Section: Photomediated and Advanced Oxidative Processes For Removing Drugs From The Kit-covidmentioning
confidence: 99%
See 3 more Smart Citations
“… Yazdani and Sayadi (2018) , in studies using sonochemistry in AZI degradation, have shown that the pH has a significant effect on the AZI degradation, while temperature and contact time have a less significant effect. The experimental conditions in which 90.59% AZI degradation was achieved were temperature = 40 ⁰C, initial concentration of AZI = 20 mg L −1 , pH = 3, after 15 min and using low-frequency ultrasound (35 kHz), as shown in Fig.…”
Section: Photomediated and Advanced Oxidative Processes For Removing Drugs From The Kit-covidmentioning
confidence: 99%
“…The experimental conditions in which 90.59% AZI degradation was achieved were temperature = 40 ⁰C, initial concentration of AZI = 20 mg L −1 , pH = 3, after 15 min and using low-frequency ultrasound (35 kHz), as shown in Fig. 11 ( Yazdani and Sayadi, 2018 ).
Figure 11 (a) Changes of HCQ with the applied electric charge during electrochemical oxidation (EO), sono-assisted electrochemical oxidation (SEO), photo-assisted electrochemical oxidation (PEO) of HCQ in aqueous solution using BDD anode ( Bensalah et al 2020 ).
…”
Section: Photomediated and Advanced Oxidative Processes For Removing Drugs From The Kit-covidmentioning
confidence: 99%
See 2 more Smart Citations
“…The pharmacological active compounds (PhACs) are an important, emerging group of organic contaminants that are persistent and show toxicity. They produce active metabolites when released into aquatic environments [ 1 , 2 ]. These compounds enter into the environment from the pharmaceutical industries, hospitals, and municipal wastewater treatment plants and after consumption in agriculture and aquaculture [ 3 ].…”
Section: Introductionmentioning
confidence: 99%